Comparison of vital signs in gymnastic participants in ac and non-ac rooms - Fernando, Fernando; Nasution, Masdalena; Lina, Juliana (Institute of Computer Science (IOCS), 2025)
Vital signs, including heart rate, blood pressure, respiratory rate, and body temperature, are essential indicators of physiological responses to exercise. Environmental conditions such as temperature and humidity may alter these responses, yet limited evidence exists regarding their effect during indoor training in tropical climates. This study aimed to analyze differences in vital sign responses between individuals performing gymnastics-based strength training in air-conditioned (AC) and non-AC fitness centers in Medan Petisah District, Medan. A quasi-experimental pretest–posttest two-group design was applied with 100 male participants aged 18–30 years who routinely engaged in gymnastics-based exercise. Participants were divided into two groups: training in AC gyms and training in non-AC gyms. Vital signs, namely heart rate, systolic and diastolic blood pressure, respiratory rate, and body temperature, were measured before and after a standardized 30-minute session. Data analysis used the Independent t-test with a significance threshold of p<0.05. The findings showed no statistically significant differences in heart rate (p=0.184), systolic blood pressure (p=0.263), diastolic blood pressure (p=0.714), respiratory rate (p=0.114), and body temperature (p=0.380) between the AC and non-AC groups. These results indicate that short-term strength training produces similar physiological responses regardless of the presence of air conditioning. Strength training in both AC and non-AC environments demonstrated comparable impacts on vital signs. Although environmental comfort may differ, acute physiological adaptation remained stable. Further studies should involve diverse participants, longer training durations, and additional physiological variables to deepen understanding.